A state-wide audit of unhealthy sponsorship within junior sporting clubs in Victoria, Australia. Issue 12 (26th August 2021) - Martino, Florentine; Chung, Alexandra; Potter, Jane; Heneghan, Tara; Chisholm, Melanie; Riesenberg, Devorah; Gupta, Adyya; Backholer, Kathryn
Abstract: Objective: To systematically audit the extent of unhealthy sponsorship within junior community sporting clubs and ascertain whether differences exist across geographical areas and sport types. Design: Club sponsorship data were assessed to determine the extent of unhealthy food/beverage, alcohol and gambling sponsorship using a cross-sectional design. Differences across geographical areas were assessed using logistic regressions. Setting: A stratified random sampling procedure was used to select thirty communities across the state of Victoria, Australia. Within each community, local clubs across the top eight participating junior sports were selected for audit. Participants: Sponsorship data were collected from 191 club websites and Facebook pages in September–November 2019. Results: Unhealthy sponsorships represented 8·9 % of all identified sponsorship arrangements. A quarter of all clubs accepted alcohol (25·6 %) and unhealthy food sponsors (25·9 %), and one-fifth of all clubs accepted high-risk food (unhealthy brands with large market share) (18·1 %) and gambling sponsors (20·4 %). Acceptance of unhealthy sponsorship differed across sport types with football, netball, cricket and soccer clubs having the greatest numbers. Compared with metro areas, a significantly greater proportion of sporting clubs in regional areas were affiliated with unhealthy food (32·7 % v . 19·6 %) and high-risk food sponsors (26·9 % v . 9·8 %). A higher proportion of clubs in low socio-economic status (SES), compared with the high SES areas, were affiliated with alcohol (33·9 % v . 16·5 %) and gambling sponsors (27·4 % v . 12·6 %). Conclusion: Victorian children participating in community junior sports are being exposed to marketing of unhealthy brands and products. Public health intervention is necessary to protect children from this exposure.